A5.04 Longitudinal in vivo multimodal [18f]FDG pet-ct imaging monitors the reversibility of systemic inflammatory processes upon tnf blockade in experimental arthritis. (24th February 2016) - Hayer, S; Zeilinger, M; Dumanic, M; Seibt, M; Niederreiter, B; Shvets, T; Smolen, JS; Hacker, M; Redlich, K; Mitterhauser, MM
Abstract : Objective: To use in vivo multimodal [ 18 F]FDG (fluoro-D-glucose) positron emission tomography/computed tomography (PET-CT) imaging for the assessment and monitoring of systemic inflammatory processes and its colocalized bone destructions before and after TNF blockade in human tumour necrosis factor transgenic (hTNFtg) mice, an established mouse model of chronic inflammatory, erosive polyarthritis. Methods: 8 week old hTNFtg mice were treated with anti-TNF antibodies (i.p., 3x times per week, 10 mg/kg body weight) for 4 weeks. Before and after the treatment period isofluran-anaesthetised hTNFtg mice and their wt littermates were used for [ 18 F]FDG PET-CT scans using an Inveon small animal PET/CT/SPECT multimodality system (Siemens Medical Solutions). Mice received [ 18 F]FDG (˜25 MBq) either by intra-venous injection for dynamic (0–90 min) or by intra-orbital injections for static PET scans (45 min post injection) followed by whole-body and high resolution leg CT scans (800 kV, 500 µA, 800 ms, 360 projections, FOV whole-body: 10 cm or legs: 4 cm, Feldkamp, Ramp filter). PET reconstructions were conducted with OSEM3D/MAP, FBP algorithm using the Inveon Acquisition Workplace software. Joints were subsequently isolated, fixed in 7% formaldehyde for 24 h and stored in 70% ethanol for ex vivo high resolution µCT imaging (Scanco µCT35, energy: 55 kVp; 145 µA, 8 W; FOV/diameter 12.3). Synovial inflammation, bone and cartilage destruction were assessed in hematoxylin-eosin (H&E), tartrate-resistant acid phosphatase (TRAP) and toluidine-blue (TB) stained paraffin-embedded joint sections. Results: Before therapeutic interventions we observed an increased accumulation of [ 18 F]FDG in various joints of hTNFtg mice including knees, ankles, shoulders, elbows, wrists, hips, iliosacroiliac and atlanto-axial joints compared to wt littermates. Four weeks after anti-TNF treatment we found a significant decrease in [ 18 F]FDG uptake in the same individuals. Fusion of PET images with CT scans demonstrated intact bone surfaces in anti-TNF-treated animals. In contrast, placebo treated hTNFtg animals showed progressed [ 18 F]FDG uptake and severe bone destructions by CT in the above mentioned joints. Therapeutic effects on synovial inflammation, bone erosion and cartilage damage were also confirmed on histological sections and µCTs. Conclusion: In vivo multimodal [ 18 F]FDG PET-CT imaging provides an objective, non-invasive imaging tool for the longitudinal monitoring of inflammatory processes and morphological features of bone destruction during therapeutic interventions in arthritic mice.